POLYCYSTIC OVARY SYNDROME AND METABOLIC SYNDROME (World Bulletin of Social Sciences, 2025)
Polycystic ovary syndrome and metabolic syndrome are considered important medical problems in modern medicine for women's health and the human body as a whole. Extensive information about the possible interrelationship of both diseases, their clinical manifestations, etiopathogenesis and the specificity of treatment methods is widely covered in research. This article provides a detailed analysis of the main features of polycystic ovary syndrome and metabolic syndrome, their relationship, diagnosis, clinical manifestations and treatment approaches